The Shadow of Death: Analysing the Pre-Exit Productivity of Portuguese Manufacturing Firms - Carreira, Carlos (2008)
In this study, we examine the pre-exiting productivity profile of mature firms relatively to survivors. We also evaluate how productivity affects the probability of exit along various dimensions. Our approach is an empirical one, and it is based on an unbalanced panel of Portuguese manufacturing firms covering a period of one decade. Our findings confirm that market selection forces low-productivity firms to exit, but there is also evidence that a sizeable portion of low-productivity firms do not shut down. Conversely, there is a non-negligible fraction of high-productivity firms that do actually close. In line, too, with some key theoretical predictions, exiting firms reveal a falling productivity level over a number of years prior to exit. Finally, our results from the survival model show that both low-productivity and small firms are much more likely to exit the market. Industry and macro environment were also found to have a non-negligible role on the exit of mature firms.